2019
DOI: 10.1016/j.bcp.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Inositol hexakisphosphate increases the size of platelet aggregates

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These highly charged small molecules include inositol-1,3,4,5,6-pentakisphosphate (IP5) and IP6. IP6 binds to numerous host cell proteins and regulates diverse biological processes, including chromatin remodeling ( 11 ), mRNA nuclear export ( 12 , 13 ), platelet aggregation ( 14 ), prion propagation ( 15 ), and circadian rhythm ( 16 ). IP6 also binds to the HIV-1 capsid in vitro and stabilizes the hexameric CA lattice.…”
Section: Introductionmentioning
confidence: 99%
“…These highly charged small molecules include inositol-1,3,4,5,6-pentakisphosphate (IP5) and IP6. IP6 binds to numerous host cell proteins and regulates diverse biological processes, including chromatin remodeling ( 11 ), mRNA nuclear export ( 12 , 13 ), platelet aggregation ( 14 ), prion propagation ( 15 ), and circadian rhythm ( 16 ). IP6 also binds to the HIV-1 capsid in vitro and stabilizes the hexameric CA lattice.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent report that IP6 can increase platelet aggregate size [ 89 ] needs to be addressed. Additionally, it appears that platelets have ability to interact with tumor cells in the circulation, contributing to the “circulome” formation [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study has revealed a role for Ins P 6 in regulation of platelet aggregate size, in a mechanism involving its interaction with fibrinogen. Although previous evidence identified both Ins P 5 and Ins P 6 as binding partners of fibrinogen [ 47 ], InsP 5 did not have a role in regulation of aggregation, which appeared specific for InsP 6 [ 46 ]. The authors suggested a role for Ins P 6 in supporting and stabilizing the crosslinking between fibrinogen and platelets, identifying this IP as a novel potential player in regulation of platelet functions [ 46 ].…”
Section: Intracellular Processes Regulated By Ips Binding To Protementioning
confidence: 94%
“…A recent study has reported the increase of Ins P 6 in platelets upon stimulation with thrombin, collagen I and ADP [ 46 ]. Importantly, this study has revealed a role for Ins P 6 in regulation of platelet aggregate size, in a mechanism involving its interaction with fibrinogen.…”
Section: Intracellular Processes Regulated By Ips Binding To Protementioning
confidence: 99%